2021
DOI: 10.3390/su13073968
|View full text |Cite
|
Sign up to set email alerts
|

Indonesians’ Perceptions of Auto Parts Remanufactured in China: Implications for Global Remanufacturing Operations

Abstract: Remanufacturing is a key strategy for achieving a circular economy. One crucial obstacle to remanufacturing is consumers’ acceptance (or non-acceptance) of remanufactured products. The current study investigated Indonesian consumers’ perceived images of remanufactured auto parts (RAPs) remanufactured in China. Consumers’ perception of a target country can be either helpful or damaging for an international business. If China seeks successful remanufacturing operations across national boundaries, it must establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…Existing RMP‐related research already provides an understanding of consumer behaviors, pricing strategies (Abbey et al., 2015; Michaud & Llerena, 2011; Neto et al., 2016; Pang et al., 2015), branding (Abbey et al., 2017; Agrawal et al., 2015), and reputation management (Subramanian & Subramanyam, 2012), and reveals factors that influence purchasing behavior (Wang et al., 2013; Jiménez‐Parra et al., 2014; Matsumoto et al., 2018a), but little attention has been paid to the influence of a country‐of‐origin effect (COE) on RMPs (Chinen & Matsumoto, 2021; Matsumoto et al., 2018a) even though the COE can vary across product types (Han & Qualls, 1985). The recent “buy domestic” campaign worldwide may influence remanufacturers’ decisions regarding facility locations for supply chain management because consumers tend to rate goods made in highly industrialized countries higher than goods from developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Existing RMP‐related research already provides an understanding of consumer behaviors, pricing strategies (Abbey et al., 2015; Michaud & Llerena, 2011; Neto et al., 2016; Pang et al., 2015), branding (Abbey et al., 2017; Agrawal et al., 2015), and reputation management (Subramanian & Subramanyam, 2012), and reveals factors that influence purchasing behavior (Wang et al., 2013; Jiménez‐Parra et al., 2014; Matsumoto et al., 2018a), but little attention has been paid to the influence of a country‐of‐origin effect (COE) on RMPs (Chinen & Matsumoto, 2021; Matsumoto et al., 2018a) even though the COE can vary across product types (Han & Qualls, 1985). The recent “buy domestic” campaign worldwide may influence remanufacturers’ decisions regarding facility locations for supply chain management because consumers tend to rate goods made in highly industrialized countries higher than goods from developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, product knowledge negatively affects perceived risk [ 91 ] and directly influences demand risk [ 41 ]. On the contrary, Chinen and Matsumoto [ 15 ] couldn’t find a significant relationship between product knowledge and perceived risk. Moreover, Wang et al [ 91 ] found that product knowledge negatively influences purchase intention.…”
Section: Tccm Analysis Of Rpmentioning
confidence: 97%
“…Wahjudi et al [ 85 ] note that there are financial (obsolescence concern, regulatory concern), quality (quality assurance, perceived quality, lack of OEM support), and social risks (prestige concern, subjective norm, public opinion, and trend concern). Chinen and Matsumoto [ 15 ] considered only physical, financial, performance, and time risks.…”
Section: Tccm Analysis Of Rpmentioning
confidence: 99%
See 2 more Smart Citations